2014
DOI: 10.1186/1471-2393-14-321
|View full text |Cite
|
Sign up to set email alerts
|

Varying gestational age patterns in cesarean delivery: an international comparison

Abstract: BackgroundWhile international variations in overall cesarean delivery rates are well documented, less information is available for clinical sub-groups. Cesarean data presented by subgroups can be used to evaluate uptake of cesarean reduction policies or to monitor delivery practices for high and low risk pregnancies based on new scientific evidence. We studied differences and patterns in cesarean delivery rates by multiplicity and gestational age in Europe and the United States.MethodsThis study used routine a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 39 publications
3
33
0
5
Order By: Relevance
“…However, evidence on these risks is not straightforward and this results in variations in obstetric intervention across countries [63]. For instance, cesarean rates for singletons 32-36 weeks were between 27% and 52% and for early term between 19% and 47% in 18 high-income countries in 2008 [64]. In one study investigating clinician-initiated deliveries, the USA displayed the highest rates of intervention among late preterm and early births (44% and 42%, respectively); compared to Sweden (24.5% and 36.9%) [23].…”
Section: Medical Practices and Policiesmentioning
confidence: 99%
“…However, evidence on these risks is not straightforward and this results in variations in obstetric intervention across countries [63]. For instance, cesarean rates for singletons 32-36 weeks were between 27% and 52% and for early term between 19% and 47% in 18 high-income countries in 2008 [64]. In one study investigating clinician-initiated deliveries, the USA displayed the highest rates of intervention among late preterm and early births (44% and 42%, respectively); compared to Sweden (24.5% and 36.9%) [23].…”
Section: Medical Practices and Policiesmentioning
confidence: 99%
“…We identified maternal and neonatal variables that have been associated with both birth weight for gestational age/gestational age and risk of intellectual disability and might therefore confound the associations under study. As a result, we extracted information on maternal age at delivery [22,23], parity [22,24], smoking during pregnancy [7,25], maternal height and weight collected at the first antenatal care visit, onset of labor [25,26], mode of delivery [25,27,28], and child's sex [22,29] from the Medical Birth Register. Body mass index (BMI) in early pregnancy [22,30] was calculated by dividing measured weight (kg) by self-reported height squared (m 2 ).…”
Section: Covariatesmentioning
confidence: 99%
“…29 Delnord et al investigated CD trends on an international level and found exceedingly high rates amongst very preterm births. 31 There are many potential underlying indications for CD in this cohort, such as malpresentation, demonstrated fetal intolerance to labor, maternal indication for immediate delivery, and higher order multiples. However, since it has been suggested by others that there may exist inherent advantage to avoidance of labor in infants of lower birth weight, the increased CD rate may also be a result of perceived benefit relative to risk.…”
Section: Discussionmentioning
confidence: 90%